Sejarah Dakwah Muhammadiyah di Palangka Raya, 1985-2020 - Salma Febylia (Syams, 2022)
This research is entitled "The History of Muhammadiyah Dawah in Palangka Raya, 1985-2020". It aims to examine the development of Muhammadiyah's dawah activities in Palangka Raya during the period of 1985-2020. Through historical research methods, the study collects and analyzes primary and secondary sources related to the history of Muhammadiyah in Palangka Raya. The findings of this study provide an overview of the growth and challenges faced by Muhammadiyah in conducting its dawah activities in the city. It also highlights the significant events and individuals who played a role in shaping the development of Muhammadiyah's dawah in Palangka Raya. This study contributes to the understanding of the history of Muhammadiyah's dawah and its role in shaping the religious and social life in Palangka Raya.Â Â